Análisis del manejo y la efectividad de la Secretaria de Gestión de Riesgo - Cujilan Henriquez, Sandy Katiusca (2020)
Social networks is one of the most widely used means of communication in recent times, which is why entities struggle for the use of them. The objective of this research is to show analysis of the management and effectiveness of the risk management secretariat and as in recent years has used social networks greatly as a simple line of control exposing citizens must be done, Developers have seen the need for the types of these types of strategies to reach areas where not all the population has access to these means. Television is another important and necessary means to know the activities carried out, but thanks to the new technologies developed television is an instrument of little use. In this work, one of the people working in the unit Mr. BOLIVAR GAVILANES is carried out, leading to the conclusion that the only purpose of the company's services is the well-being of the people. This institution for good strategic communication, also used as alternative social networks such as Facebook, Instagram, promotional videos on the YouTube platform. Therefore, this case analysis used the research of the SNGR's digital platform.